2014
DOI: 10.1093/icvts/ivu113
|View full text |Cite
|
Sign up to set email alerts
|

Resection of a bronchogenic cyst in the first decade of life with robotic surgery

Abstract: The conventional surgical approach for the removal of bronchogenic cyst in children is thoracotomy. Video-assisted thoracoscopic surgery is still under debate with the concerns of incomplete removal and injury to major intrathoracic structures. In this case report, we present an 8-year old patient who was successfully treated with robotic surgery (Intuitive Surgical, Mountain View, CA, USA). Robotic technology enables precise dissection and complete resection of the thoracic bronchogenic cyst without violating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…However, many studies have reported that robotassisted surgery is safe and feasible for pediatric patients. RATS has previously been described as part of a series of general pediatric surgeries or a series of various thoracic pathologies [22,23,26,27] , a series of pediatric cases of specific procedures such as thymectomy for myasthenia gravis [28,29] , tracheopexy for treatment of severe tracheomalacia [30] , or as pediatric case reports on esophageal leiomyoma and bronchogenic cyst [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies have reported that robotassisted surgery is safe and feasible for pediatric patients. RATS has previously been described as part of a series of general pediatric surgeries or a series of various thoracic pathologies [22,23,26,27] , a series of pediatric cases of specific procedures such as thymectomy for myasthenia gravis [28,29] , tracheopexy for treatment of severe tracheomalacia [30] , or as pediatric case reports on esophageal leiomyoma and bronchogenic cyst [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the detailed non-systematic review of previous publications in PubMed on noncardiovascular thoracic pathology treated with robotic surgery in the pediatric population worldwide, currently, the number of children treated with this technology barely has reached 100 cases, and all related references with the theme are included [11,22,[26][27][28][29][30][31][32][33][34]36,39,44,45] .…”
Section: Congenital Diaphragm Abnormalities Including Eventration Anmentioning
confidence: 99%
“…Lin et al reported the successful thoracoscopic resection of two bronchogenic cysts in the upper mediastinum without postoperative complications (11). With many reports of cases treated successfully, Toker et al reported the resection of a bronchogenic cyst in an 8-yearold patient with robotic surgery (6).…”
Section: Discussionmentioning
confidence: 99%
“…Toker et al .,[ 11 ] reported their experience with robotic assisted excision of a sub-carinal bronchogenic cyst. They concluded the da Vinci Surgical System for such indications, especially for patients who are in the first decade of their life, may provide higher technical capabilities in a smaller room when compared with VATS.…”
Section: Discussionmentioning
confidence: 99%